A flexible visual quality control algorithm for perceptual video encryption based on H.264. (2018) - Cao, Yuqiang; Gong, Weiguo; Bai, Sen
In order to meet all kinds of video security applications, especially pay-digital-TV system, a perceptual video encryption scheme based on visual quality control strategy is proposed. The optimal syntax elements and sensitive coded elements are chosen to encrypt by using mathematical XOR operations with stream ciphers generated by Chen chaos system. In order to enhance the security, the encryption scheme of this paper synthetically uses three strategies, including Motion Vector Difference (MVD) encryption, intra prediction mode encryption and levels of low coefficients encryption. The variable length keys are used to encrypt the syntax elements to improve key utilisation. Experimental results show that the proposed perceptual encryption scheme can achieve high security at a relatively high compression ratio and bandwidth cost, as well as about 2% coding rate and 6% encoding time increased at the cost of slightly sacrificing code rate and encoding time. Especially, the degraded visual quality can be controlled gradually with a simple quality factor.